Evaluasi Jalan Rabat Beton baru pada STA 2.000 -STA 3.000 di JalanJambuara Nagori Buntu Bayu Kecamatan Hatanduhan KabupatenSimalungun - Nizar, Asril; E. Purba, Virgo (Teknik Sipil Universitas Simalungun, 2020)
Roads are the main means of transportation to reach a destination from one place to another for any traffic that passes through it. Therefore, road conditions greatly affect the safety and security of every road user. Concrete slabs that are stiff and have a high modulus of elasticity will distribute traffic loads over a fairly large area of ​​the subgrade. Thus, most of the capacity of the pavement structure is obtained from the concrete slab itself. In contrast to flexible pavement, the strength of the pavement is obtained from the thickness of the subbase layer, foundation layer and surface layer; where each layer makes its contribution. Observations carried out on Jalan Jambuara Nagori Buntu Bayu, Hatonduhan District, Simalungun Regency were aimed at the implementation stages of concrete road construction. In the construction of this road, rigid pavement with ready-mix concrete was used.